(untitled) (Journal of Social Sciences Review, 2025)
This study investigated the relationship between the attitudes of government girls’ secondary school students towards learning mathematics and their academic achievement. The population of the students consisted of all female students studying in government schools in the district of Malakand. A sample of 300 students selected from 20 schools were randomly selected. An adapted questionnaire related to attitudes toward mathematics developed by Ali (2008) was used to collect data from the sampled students. Students’ marks obtained in the subject of mathematics in the annual examination held under the Board of Intermediate & Secondary Education (BISE), Malakand, are used as a measure of students’ academic achievement. The reliability of the questionnaire was established through Cronbach’s alpha, which was found to be .96. The study revealed a positive attitude towards girls’ students towards the subject of mathematics. A positive, moderately significant relationship was found between the attitude of female students towards mathematics and academic achievement. The study recommended that mathematics teachers use interactive and inquiry-related activities in class to present mathematics as an interesting and creative subject that will be useful for them in the future.